EDUKASI POLA ASUPAN MAKANAN MEMPENGARUHI KADAR VITAMIN D DAN KUALITAS HIDUP ANAK PADA MASA GROWTH SPURT KEDUA - Adinda Tri Nindia (CV. Adiba Aisha Amira, 2024)
Micronutrients, including vitamin D. So far, the evaluation of vitamin D has received little attention, if it is worsened by indoor activity patterns and unbalanced food consumption patterns, it is feared that it will trigger vitamin D deficiency and have an impact on children's growth and development and quality of life. . life. To determine the relationship between children's consumption patterns and vitamin D levels, body weight, height and quality of life in children aged 10-12 years. This type of research is descriptive qualitative with interview and observation methods as data collection techniques. Interviews were conducted with informants, using 40 subjects, namely children during the second growth spurt period. All subjects had their consumption patterns measured using the Food Frequency Questionnaire (FFQ), vitamin D levels in the blood, height, weight, leg length, and Quality of life was measured using the Pediatric Quality of Life Inventory (PedsQL). The results showed that of the 40 subjects, only 3 (7.5%) children had sufficient vitamin D levels (≥30 µg/mL). There is a significant relationship between food consumption patterns and blood vitamin D levels. Children's food consumption patterns during the second growth spurt need to be considered because they are related to vitamin D levels, height, weight and quality of life.